TALL FESCUE GRASS AND WHITE CLOVER BASED MIXED CROPPING STANDS UNDER THE INFLUENCE OF POPULATION DYNAMICS - Naveen Kumar; Rajiv Kumar Agrawal; Ajoy Kumar Roy; Tarun Sharma; Sukhchain Singh; Shwetansh (Journal of Animal and Plant Sciences, 2025)
India has been a global leader in milk production owing to its largest livestock population. However, availability of quality forage has been a major constraint in limiting livestock productivity which can be attributed to low nutritive value and productivity of conventional forage cropping systems based solely on grasses. Therefore, the present study was carried out over a period of 5 years to evaluate the productivity, nutritive value and profitability of tall fescue grass and white clover based mixed cropping systems under the influence of varying planting geometries and seed rates. Eleven treatments based on variable combinations of spacing and seed rate of tall fescue grass (20 x 30, 30 x 30 and 40 x 40 cm) and white clover (1, 2 and 3 kg/ha) were evaluated under randomized complete block design (RCBD) involving three replications of each treatment. The outcomes of the present investigation revealed that TFG 30x30 cm + WC 2.0 kg/ha-based mixed planting practice performs significantly better in terms of total forage harvest, crude protein yield and profitability attained, which can be primarily attributed to complementary relationship between forage grasses and legumes. The present investigation further revealed that total available nitrogen was considerably improved under sole planting of white clover and TFG 30x30 cm + WC 3.0 kg/ha based mixed cropping. Therefore, the current field study concluded TFG 30x30 cm + WC 2.0 kg/ha based mixed cropping system as the standout one to yield considerable higher levels of quality forage as well as enhanced farmer incomes especially in terms of gross and net returns when compared to conventional sole TFG based cropping systems.
Keywords: Forage; mixed cropping; nutritive value; tall fescue grass; white clover